ANALISIS EFISIENSI MODAL KERJA PADA KOPERASI PEGAWAI REPUBLIK INDONESIA (KPRI) BETIK GAWI DINAS PENDIDIKAN KOTA BANDAR LAMPUNG - Hairudin, Hairudin; Desmon, Desmon (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2020)
The purpose of this study is to determine working capital which is a supporting factor in cooperative activities. In achieving its objectives, it is not only limited to efforts to obtain funds but also the use of funds that must be economically viable so as to achieve maximum efficiency. The analysis used in this study is the performance of the working capital turnover of cooperatives. The results of this study are reviewed from the working capital turnover ratio of cooperatives, working capital turnover ratios in service transactions and working capital turnover ratios on business transactions for employees of the Republic of Indonesia (KPRI) betik gawi city education. Department of Cooperative Bandar Lampung shows the average ineffective conditions and efficient in valuation compared to the previous year.Keywords: working capital, cooperatives, working capital efficiency